Measures of Material Deprivation in OECD Countries - Boarini, Romina; d'Ercole, Marco Mira. (Παρίσι : OECD Publishing, 2006)
Poverty is a complex issue, and a variety of approaches are required for its measurement and analysis. While monetary measures of income poverty are widespread, a long-standing tradition relies on non-monetary measures, based on either the respondent's self-assessment of their own conditions or on measures of ownership of consumer goods and living standards. Measures of material deprivation fall into this latter category. These measures rest on shared judgments about which items are more important to provide a "decent" living standard, irrespective of people's preferences and of their capacity to afford these items. Material deprivation is typically the outcome of income poverty when this persists over time, or when individuals experience repeated spells of it. Because of this, measures of material deprivation add important information to that provided by conventional income measures, permitting an assessment of poverty from a longer-run perspective and furthering understanding of the causal mechanisms at work.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Migration -- OECD Countries; Employment -- OECD countries; Electronic books